Environmentally benign synthesis of vinyl ester resin from biowaste glycerin1. Issue 48 (28th May 2015) - Shah, Priyank N.; Kim, Namjoon; Huang, Zhuangrong; Jayamanna, Mahesh; Kokil, Akshay; Pine, Alex; Kaltsas, Jarmin; Jahngen, Edwin; Ryan, David K.; Yoon, Seongkyu; Kovar, Robert F.; Lee, Yongwoo
<x xml:space="preserve">Abstract</x> We present here for the first time a novel environmentally benign protocol for the synthesis of vinyl ester resin (VER).